Schooling for money: Swedish education reform and the role of the profit motive - Gabriel H. Sahlgren (Institute of Economic Affairs (IEA), 2011)
An analysis of how the profit motive drove competition and therefore improvements in the Swedish education systemThis IEA Discussion Paper looks at the role of for-profit schools in Sweden and for the first time provides quantitative evidence regarding how these schools perform. The competition that drove improvements in the Swedish system was only possible because of the high number of for-profit schools that were established.This research clearly shows that:Under a system where profit is allowed more children have access to schools that will improve their educational achievement.For-profit schools make the competition that drives up standards possible by increasing the supply of new schools.Importantly the impact of for-profit schools tends to be greatest on those from low socio-economic backgrounds.The educational outcomes of children going to for-profit and not-for-profit schools were significantly better than those of children going to state schools (measured in terms of average school GPA, which measures pupil achievement across a broad range of subjects).Not-for-profit schools did marginally better on average than for-profit schools (raising the GPA by 5.7 points compared with the for-profit schools' impact of 4.5 points), but among schools with pupils from lower socio-economic backgrounds, for-profit schools performed better (increasing the GPA by 11.6 points).In the English education system there are around 24,600 schools; back in August this year only 62 free school applications had been made. This highlights the desperate need to encourage new schools to start up. The case of Sweden shows that increasing the supply of new schools to create sufficient competition in the system to raise standards requires encouraging schools to start up with a profit motive, yet at present this is being excluded by the coalition. In Sweden during 2008/2009 13% of schools were for-profit, while only 6% were non-profit schools. If England encouraged for-profit schools we could see a similar take up which could mean around 3,200 new schools.
Keywords: 330; Education; Education reform; Costs; Economic efficiency; Sweden; Bildungswesen; Bildungsreform; Kosten; Wirtschaftlichkeit; Schweden